Передача даних та енергії в системах бездротової передачі енергії - Сокіркаєв, Д. В. (ХНУРЕ, 2025)
The development of wireless power transmission (WPT) technologies opens up new opportunities for creating autonomous power systems that do not require physical connections. This is especially important for electric vehicles, medical implants, mobile devices, and industrial applications. However, the effective implementation of the WPT requires not only a stable power supply, but also reliable data exchange between devices. To ensure the reliability of WPT systems, simultaneous wireless power and data transmission technology has attracted increasing attention to realize real-time information exchange between the transmitter and receiver.
Keywords: передача енергії; бездротова передача енергії